Upaya Mengatasi bahaya Pernikahan Dini dan Kenakalan Remaja di Desa Gunung, Kecamatan Simo, Boyolali - Yanitama, Arka; Rafael Eben Haezer Ginting; Tanti Liana Dewi; Umi Sa’adah; Charles Sahalatua Pangaribuan (Universitas Negeri Semarang, 2024)
Early marriage and juvenile delinquency are two phenomena that often traverse different paths but have the potential to cast a dark shadow on the social development of society. Early marriage and juvenile delinquency are not simply social phenomena that can be ignored; both haunt the future of the younger generation and place a heavy burden on the well-being of society as a whole. In this article, we will explore in depth the dangers of early marriage and juvenile delinquency, uncover the roots of the problem, and detail the negative impacts on individual and societal development. In this community activity, the UNNES GIAT 6 KKN Team and the Gunung Village Government collaborated to carry out an outreach with the theme